ANALISIS PERAN MEDIASI RESISTENSI DALAM FAKTOR-FAKTOR PEMBENTUK NIAT PENGGUNAAN (SURVEY PENGGUNA APLIKASI MOBILE LEARNING DI INDONESIA) - Salman faris Insani (Departemen Manajemen, 2022)
The purpose of this research is to test and analyze the mediating role of resistance in the factors influencing intention use mobile learning which includes relative advantages, complexity, inertia, and innovative. The sample in this study was 171 high school students in Indonesia. The sampling method used is non-probability sampling, while the technique used is purposive sampling. Hypothesis testing in this study using Structural Equation Modeling. Results of this study shows that the complexity has an effect on intention to use mobile learning and inertia affect mobile learning resistance. Relative advantages and innovative has no effect on intention to use mobile learning. In addition, the relative advantages and complexity has no effect on mobile learning resistance. Mobile learning resistance does not mediate the relative advantage effect on intention to use mobile learning, whereas mobile learning resistance partially mediates the effect of complexity on intention to use mobile learning.